Orthodontic tooth movement in relation to angular bony defects - Michelogiannakis Dimitrios; Makou Margarita; Madianos Phoebus N.; Rossouw P. Emile (Sciendo, 2017)
This review provides a comprehensive assessment of the benefits of adjunctive orthodontic treatment with or without periodontal regenerative surgery in the treatment of angular bony defects, defect volume, and periodontal tissue conditions in adult patients.